Time-Resolved and Micro-Scale Measurement of Thermal Property for Intermolecular Dynamics Using an Infrared Laser - Masahiro MOTOSUKE; Yuji NAGASAKA; Shinji HONAMI (Journal of Thermal Science and Technology, 2008)
This paper describes a time-resolved measurement of thermal property in microscale during reaction processes of polymer by using an infrared (IR) laser. Polymer or gel-like material, so-called macromolecules, have diversity in its structure and intermolecular association, and recent development of measurement and control technique in micro- and nano- scale has opened up new possibilities for the property design of materials. The intermolecular dynamics of polymer can be reflected in time-resolved information of the thermal conductivity or thermal diffusivity. A measurement system of the thermal diffusivity in real-time and non-contact manner based on the forced Rayleigh scattering (FRS) method has been developed. This system can be applied for a changing process of a wide variety of polymer material because of employing a CO2 laser with the IR wavelength. Also, it is possible to measure the micro-scale property. By using the IR-FRS system, an investigation of the relationship between intermolecular dynamics of macromolecules and energy transfer can be conducted through the time-resolved data of the thermal diffusivity. As samples, crosslinking processes of a polysaccharide aqueous solution and an ultraviolet curable polymer were measured. In these processes, the samples change their microstructure by hydrogen and covalent bonding, respectively. Time evolution of the measured thermal property from the IR-FRS system clearly indicated the difference in bonding modes of macromolecules. According to the time-resolved measurement results, the validity of this technique for a versatile instrument of intermolecular dynamics of macromolecules is demonstrated.